Pengaruh Current Ratio (CR) dan Debt to Equity Ratio (DER) Terhadap Profitabilitas Pada Industri Terindeks LQ 45 - Rina Faujiah; Nursito Nursito (Jurnal Dinamika Ekonomi & Bisnis, 2022)
Industries indexed by LQ 45 are industries that have a very large market capitalization value. This is what causes investors to compete to invest their shares in the LQ 45 indexed industry. Therefore, this study aims to see whether the Current Ratio and Debt to Equity Ratio have a contribution to profitability. In taking the sample using purposive sampling method with several criteria so as to get 6 samples of the manufacturing industry in the consumer goods sector. In analyzing the data using the classical assumption test, multiple linear regression analysis and hypothesis testing. The data obtained were obtained directly from the official website of each manufacturing industry in the consumer goods sector which was used as a sample in the form of the company's annual report. The results of this study partially show the current ratio has a significant contribution to profitability, the debt equity ratio also has a significant contribution to profitability. Simultaneously, the current ratio and debt equity ratio have a significant contribution to profitability of 54.8%. influenced by other factors not tested in this study.